The Effect of Mucosal Flap Technique in External Dacryocystorhinostomy on Surgical Success: “H” Flap Versus “U” Flap (Annals of Medical Research, 2021)
None
Keywords: External Dacryocystorhinostomy; Mucosal Flap Technique; U-Flap; H-Flap.